Defect Analysis Using Fault Tree Analysis and Failure Mode Effect Analysis in Rubber Roll Production - Rr. Rochmoeljati; Isna Nugraha (Nusantara Science and Technology Proceedings, 2023)
XYZ is a company operating in the manufacturing and rubber roll service industry located in Indonesia. The frequent issue within the company is the occurrence of product rejects, leading to inefficient production processes. The research is conducted using the Fault Tree Analysis (FTA) method with recommendations for improvement from the Failure Mode and Effect Analysis. This method is employed to identify the causes of product rejection and provide preventive solutions to avoid such rejections. There are three types of rejects at PT. XYZ, namely blisters rejection with a probability of 1.137%, material impurities rejection with a probability of 1.18%, and PU rejection with a probability of 1.152%. The root causes of these rejections include operators rushing, operator fatigue, machines in need of maintenance, very short production deadlines, operator laziness, incomplete environmental cleanliness facilities, and operators joking around while working. As for recommendations to reduce and prevent the recurrence of these three types of rejections, they include regular machine maintenance, providing customers with longer estimated completion times than the actual estimates, and offering rewards to operators who meet targets without making errors.